Influence of Shape Anisotropy on Magnetization Dynamics Driven by Spin Hall Effect - X. G. Li; Z. J. Liu; X. Y. Xie; A. G. Kang; W. N. Fu (Advances in Materials Science and Engineering)
As the lateral dimension of spin Hall effect based magnetic random-access memory (SHE-RAM) devices is scaled down, shape anisotropy has varied influence on both the magnetic field and the current-driven switching characteristics. In this paper, we study such influences on elliptic film nanomagnets and theoretically investigate the switching characteristics for SHE-RAM element with in-plane magnetization. The analytical expressions for critical current density are presented and the results are compared with those obtained from macrospin and micromagnetic simulation. It is found that the key performance indicators for in-plane SHE-RAM, including thermal stability and spin torque efficiency, are highly geometry dependent and can be effectively improved by geometric design.